Size Matters: Biological and Food Safety Relevance of Leaf Damage for Colonization of Escherichia coli O157:H7 gfp+ - Mulaosmanovic, Emina; Windstam, Sofia T.; Vågsholm, Ivar; Alsanius, Beatrix W. (Frontiers in Microbiology, 2021)
This study examined the biological and food safety relevance of leaf lesions for potential invasion of food pathogens into the plant tissue (internalization). This was done by determining the role of artificial leaf damage in terms of damaged leaf area on proliferation of E. coli O157:H7gfp+. In a two-factorial experiment, unwashed fresh baby leaf spinach (Spinacia oleracea L.) was subjected to four damage levels (undamaged, low, moderate, high damage; factor 1) and three incubation intervals (0, 1, 2 days post-inoculation; factor 2). Individual leaves were immersed for 15 s in a suspension loaded with E. coli O157:H7gfp+ (106 CFU × mL-1). The leaves were analyzed individually using image analysis tools to quantify leaf area and number and size of lesions, and using confocal laser scanning and scanning electron microscopy to visualize leaf lesions and presence of the introduced E. coli strain on and within the leaf tissue. Prevalence of E. coli O157:H7gfp+was counted using a culture-dependent technique. The results showed that size of individual lesions and damaged leaf area affected depth of invasion into plant tissue, dispersal to adjacent areas, and number of culturable E. coli O157:H7gfp+ directly after inoculation. Differences in numbers of the inoculant retrieved from leaf macerate evened out from 2 days post-inoculation, indicating rapid proliferation during the first day post-inoculation. Leaf weight was a crucial factor, as lighter spinach leaves (most likely younger leaves) were more prone to harbor E. coli O157:H7gfp+, irrespective of damage level. At the high inoculum density used, the risk of consumers’ infection was almost 100%, irrespective of incubation duration or damage level. Even macroscopically intact leaves showed a high risk of infection. These results suggest that the risk to consumers is correlated with how early in the food chain the leaves are contaminated, and the degree of leaf damage. These findings should be taken into account in different steps of leafy green processing. Further attention should be paid to the fate of viable, but non-culturable, shigatoxigenic E. coli on and in ready-to-eat leafy vegetables.